2015
DOI: 10.1016/j.brainres.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Midbrain dopamine neurons in Parkinson׳s disease exhibit a dysregulated miRNA and target-gene network

Abstract: The degeneration of substantia nigra (SN) dopamine (DA) neurons in sporadic Parkinson’s disease (PD) is characterized by disturbed gene expression networks. Micro(mi)RNAs are post-transcriptional regulators of gene expression and we recently provided evidence that these molecules may play a functional role in the pathogenesis of PD. Here, we document a comprehensive analysis of miRNAs in SN DA neurons and PD, including sex differences. Our data show that miRNAs are dysregulated in disease-affected neurons and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 99 publications
(83 reference statements)
3
87
0
Order By: Relevance
“…miRNAs impact on α-synuclein expression raises the hypothesis that dysregulated miRNAs in PD patients are responsible for α-synuclein upregulation and/or accumulation. Supporting this idea, several studies have demonstrated that PD patients exhibited dysregulated miRNAs in brain (Kim et al, 2007; Cardo et al, 2013; Miñones-Moyano et al, 2013; Briggs et al, 2015; Hoss et al, 2016), blood (Margis et al, 2011; Martins et al, 2011; Khoo et al, 2012; Botta-Orfila et al, 2014; Burgos et al, 2014), cerebrospinal fluid (CSF; Burgos et al, 2014; Gui et al, 2015; Hossein-Nezhad et al, 2016) and medulla (Liao et al, 2013). …”
Section: Discussionmentioning
confidence: 93%
“…miRNAs impact on α-synuclein expression raises the hypothesis that dysregulated miRNAs in PD patients are responsible for α-synuclein upregulation and/or accumulation. Supporting this idea, several studies have demonstrated that PD patients exhibited dysregulated miRNAs in brain (Kim et al, 2007; Cardo et al, 2013; Miñones-Moyano et al, 2013; Briggs et al, 2015; Hoss et al, 2016), blood (Margis et al, 2011; Martins et al, 2011; Khoo et al, 2012; Botta-Orfila et al, 2014; Burgos et al, 2014), cerebrospinal fluid (CSF; Burgos et al, 2014; Gui et al, 2015; Hossein-Nezhad et al, 2016) and medulla (Liao et al, 2013). …”
Section: Discussionmentioning
confidence: 93%
“…MicroRNA-181a has been shown to be dysregulated in PD patients, suggesting that it may contribute to the underlying pathology, while it has also been proposed as a potential disease biomarker [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…We first sought to gain insight into the biological processes that may be altered by elevated miR-181a expression in the mDA neurons in PD [13]. To do this, we used miRecords to create a list of putative miR-181a mRNA targets predicted by at least four prediction programs [20].…”
Section: In Silico Analysis Implicates Mir-181a As a Regulator Of Bmpmentioning
confidence: 99%
See 1 more Smart Citation
“…One conserved ncRNA pathway was identified through miRNA expression profiles of midbrain dopamine neurons (mDNs) in PD patients (Kim et al, 2007; Briggs et al, 2015). One of the dysregulated miRNAs, miR-133b, controls mDN differentiation through a feedback loop with Pitx3 (Kim et al, 2007).…”
Section: Mirna-mediated Regulation Of Dopamine Signaling In Neurologimentioning
confidence: 99%